Protection against bacterial soft rot by olive extracts is related to general defence induction in potato tubers. (17th August 2016) - Ouanas, S.; Hamelin, G.; Hervet, M.; Andrivon, D.; Val, F.; Yahiaoui‐Zaidi, R.
Abstract : Controlling bacterial plant diseases remains a challenge, as direct chemical control is usually not possible. Obtaining new biocontrol methods, in particular efficient biomolecules able to boost defence reactions and limit infection or symptom development, is therefore of major importance. This study screened extracts from leaves of two Mediterranean plants rich in bioactive phenolic compounds, olive and carob, for their ability to reduce soft rot severity and to trigger phenylalanine ammonia‐lyase (PAL) activity in potato tuber slices. Extracts from olive leaves significantly reduced disease severity caused by Pectobacterium atrosepticum or Pectobacterium carotovorum, whereas carob leaf extracts significantly increased it. Olive extracts and its main phenolic components, oleuropein and hydroxytyrosol, also significantly increased PAL activity 7.5 h after application. None of the extracts or purified molecules reduced bacterial growth in vitro . Furthermore, the effect of these extracts varied according to potato cultivars. These data therefore open new ways for the biological control of soft rot bacteria, but stress the importance of understanding the causes of response difference in different potato varieties in order to obtain optimal efficacy.